Characteristics of primary tin mineralization in the Central and West Bangka Island. Issue 1 (July 2020) - Aditya, R; Setiawan, I; Nugraheni, R D; Sihombing, F M H; Indra, T L
Abstract: Bangka Island is an important tin producer in Indonesia, mostly from the secondary tin deposits. However, the secondary tin deposit is depleting, causing further exploration shifted to the primary tin mineral. The purpose of this study is to make a mineralization model of primary tin deposit in Bangka Island. Methods that implemented in this study are petrographic analysis, mineragraphic analysis, XRD (X-Ray Diffraction), and XRF (X-Ray Fluorescence) analysis. The studied rock samples that consisted of granite, meta-sandstone, and sandstone. Some of the rocks are altered rocks with varying intensity. Petrographic and mineragraphic analysis show the presence of minerals that indicate the primary tin deposits, such as cassiterite, tourmaline, topaz, sericite, pyrite, and sphalerite. XRF analysis shows data about the value of Sn elements so that they can be classified into two classes, very high grade (> 800 ppm), and low grade (100–200 ppm). XRD analysis is necessary to do to determine the type and intensity of alterations that occur in the study area. The results of each analysis will provide supporting information regarding the primary tin mineralization process in Bangka Island.